PENGARUH OSIS TERHADAP PEMBENTUKAN KARAKTER TANGGUNG JAWAB SISWA PENGURUS OSIS SMPN 40 PEKANBARU - Jayanti, Yuniar; Zahirman, Zahirman; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Research is motivated by several phenomena, namely the lack ofsolidity between management, understanding between management and job description,coordination between OSIS coaches and student council officials, clarity andunderstanding of work programs by OSIS chairmen, and the academic andorganizational schedule arrangements that are not optimal. This study aims todetermine the effect of OSIS on the formation of the character of responsibility towardsthe student council students of SMPN 40 Pekanbaru. This research method isquantitative descriptive with data collection techniques namely questionnaire,observation, and documentation. The number of samples studied were 35 people. Basedon the OSIS variable questionnaire calculation with respondent data that answers theanswers very often added up with the answers frequently is 81.7%, which in the OSISvariable is included in the very good category. Next, the responsibility charactervariable at SMPN 40 Pekanbaru is included in good category. This is because theresults of the answers very often added up with the answers frequently amounting to71.3%. Furthermore, the results from the test of the significance of simple linearregression reveal that Fcount <Ftable, or 2,465 <4.14, thus Ho is accepted and Ha isrejected which means that the variable X has no effect on the variable Y. Therefore, thehypothesis in this study was not accepted.Key Words: OSIS, Character of Responsibility